2021
DOI: 10.3389/fncel.2021.691711
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Organization of the Rat Subfornical Organ

Abstract: The subfornical organ (SFO) is a sensory circumventricular organ located along the anterodorsal wall of the third ventricle. SFO lacks a complete blood-brain barrier (BBB), and thus peripherally-circulating factors can penetrate the SFO parenchyma. These signals are detected by local neurons providing the brain with information from the periphery to mediate central responses to humoral signals and physiological stressors. Circumventricular organs are characterized by the presence of unique populations of non-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 133 publications
(220 reference statements)
3
13
0
Order By: Relevance
“…Pekny (2001) found that a lack of GFAP decreases the effect of BBB. Similar differences were found in the OVLT (Kálmán et al, 2019;Prager-Khoutorsky & Bourque, 2015) and, although less consequently, in the SFO (Hicks et al, 2021;Pócsai & Kálmán, 2015).…”
Section: Differences In the Perivascular Glia Of The Different Vascul...supporting
confidence: 82%
See 1 more Smart Citation
“…Pekny (2001) found that a lack of GFAP decreases the effect of BBB. Similar differences were found in the OVLT (Kálmán et al, 2019;Prager-Khoutorsky & Bourque, 2015) and, although less consequently, in the SFO (Hicks et al, 2021;Pócsai & Kálmán, 2015).…”
Section: Differences In the Perivascular Glia Of The Different Vascul...supporting
confidence: 82%
“…In the AP, both components occur in the lateral border zone, whereas in the SFO and OVLT only narrow strips along the borderlines of the peripheral and central areas displayed immunopositivity to both GFAP and vimentin. In the OVLT this characteristic was shown by the rostroventral part adjacent to the optic chiasm (Prager‐Khoutorsky & Bourque, 2015), whereas in the SFO by the ventromedially located glial population (Hicks et al., 2021) . In the AP, the junctional ventral zone (at McKinley et al., 2003; Morita et al., 2016; “commissural NTS” at Dallaporta et al., 2010) displays similar mixed patterns of GFAP and vimentin like the lateral border zone.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that pericyte coverage determines vascular permeability, 70 and established the key role of pericytes in maintaining the BBB. 71 However, since sensory CVOs lack a complete BBB due to the presence of a dense population of leaky capillaries, 54,55,72 the role of pericytes in these areas remains ambiguous. It is conceivable that CVO pericytes have additional functions requiring constitutive renewal and/or proliferation.…”
Section: Ovlt and Sfo Represent New Adult Neurogenesis Areasmentioning
confidence: 99%
“…ANG II/AT 1 R signalling has also been implicated in food intake and metabolic control 2,3 . One of the main brain sites for peripheral ANG II action is the subfornical organ (SFO), a circumventricular structure related to the control of several autonomic functions, neuroendocrine regulation and behavioural responses 4,5 . Nevertheless, other brain regions associated with neuroendocrine control of hydromineral and metabolic balance also express AT 1 Rs and are directly and/or indirectly (via SFO) responsive to ANG II, such as the hypothalamic paraventricular nucleus (PVN) and the arcuate nucleus (ARC) 6–8 .…”
Section: Introductionmentioning
confidence: 99%
“…2,3 One of the main brain sites for peripheral ANG II action is the subfornical organ (SFO), a circumventricular structure related to the control of several autonomic functions, neuroendocrine regulation and behavioural responses. 4,5 Nevertheless, other brain regions associated with neuroendocrine control of hydromineral and metabolic balance also express AT 1 Rs and are directly and/or indirectly (via SFO) responsive to ANG II, such as the hypothalamic paraventricular nucleus (PVN) and the arcuate nucleus (ARC). [6][7][8] In the PVN, ANG II stimulates the activity and release of vasopressin (AVP), oxytocin (OXT) and corticotrophin-releasing hormone (CRH) secretion, 9 whilst in the ARC it modulates resting metabolic rate by acting on the Agouti-related peptide (AGRP)-producing neurones.…”
Section: Introductionmentioning
confidence: 99%